HIV-specific humoral immune responses by CRISPR/Cas9-edited B cells - Hartweger, Harald (J Exp Med, 2019)
A small number of HIV-1–infected individuals develop broadly neutralizing antibodies to the virus (bNAbs). These antibodies are protective against infection in animal models. However, they only emerge 1–3 yr after infection, and show a number of highly unusual features including exceedingly high levels of somatic mutations. It is therefore not surprising that elicitation of protective immunity to HIV-1 has not yet been possible. Here we show that mature, primary mouse and human B cells can be edited in vitro using CRISPR/Cas9 to express mature bNAbs from the endogenous Igh locus. Moreover, edited B cells retain the ability to participate in humoral immune responses. Immunization with cognate antigen in wild-type mouse recipients of edited B cells elicits bNAb titers that neutralize HIV-1 at levels associated with protection against infection. This approach enables humoral immune responses that may be difficult to elicit by traditional immunization.